Golay sequences - side-lobe - canceling codes for ultrasonography - Trots, I.; Nowicki, A.; Secomski, W.; Litniewski, J. (Archives of Acoustics, 2004)
In this paper three different methods and algorithms used to calculate the pairs of Golay sequences of the different length are described. The program for simulating the pairs of the Golay sequences of different length is given. This program (using Matlab[ampersand]trade; routines) is based on the basic properties of complementary series and is simple and computationally effective. Experimental results are presented in the form, which in a clear way illustrates the resolution, depth penetration and contrast dynamics of ultrasonic images obtained using the Golay coded excitation.